Clinical characteristics and outcome of Thai patients with acute pulmonary embolism - Suree Sompradeekul (2018)
Background: The incidence and clinical features of acute pulmonary embolism (APE) in Thailand are unknown. There was an unsubstantiated belief that APE in Thailand did not occur as frequently as reported in European countries. With new diagnostic tools and current advanced knowledge, APE was discovered to be much more frequent in Thailand than earlier believed. A subgroup of patients with massive APE who presented with systemic arterial hypotension tended to have poor prognosis. Clinical outcome predictor of massive APE had not been previously firmly identified. Study design: Cross-sectional study. Objectives: To evaluate common risk factors, symptoms, signs, commonly used investigations, treatment and outcome of Thai patients with APE. To compare the clinical characteristics of non-massive and massive APE patients. To identify the clinical characteristics and treatment that may predict the mortality of massive APE. Material and Method: All patients with confirmed APE diagnoses who were admitted to Siriraj Hospital, Bangkok, Thailand between January 2001 and October 2005 were selected for analysis in the present study. All APE patients' data, including demographics, symptoms, signs, investigations, treatments, outcome and risk factors such as malignancy, surgery, immobilization, and congenital thrombophilia, were recorded. Statistical analysis: Patients data is presented in the form of percent and mean. Fisher's exact test was used to compare the categorical data between massive and non-massive APE groups. T-test was used to compare continuous variable i.e. RVSP between subgroups. Results: Seventy-one patients had a confirmed diagnosis of APE, 22 patients were male and 49 were female. Fourteen patients were diagnosed with massive APE. The ages of patients varied from 16 to 90 years old. The mean age was 50+12.2 years old. The most common presenting symptoms and signs were dyspnea (92%), followed by tachypnea (63%) and tachycardia (54%). Idiopathic APE was found in 42.2% of the patients. Malignancy, especially adenocarcinoma, was the most frequent risk factor (21%). The most frequent radiographic abnormalities noted in the present study were pulmonary parenchymal lesions (23.9%). Echocardiography findings were mostly elevated right ventricular systolic pressure (RVSP), ranging from 18.5 to 98 mmHg (mean RVSP of 54.4 mmHg). The most frequent diagnostic test used was ventilation-perfusion lung scan. Elevated serum troponin-T seemed to be more frequent in the massive APE group. In the nonsurvivor group, the author found hypotension and underlying malignancy statistically significant different from the survivor group. Conclusion: APE was not infrequent. Characteristics of APE patients in Thailand were not different from previous reports in European countries. Malignancy seemed to be the most frequent risk factors of APE in the present study population. Troponin-T measurement may be useful to predict progression of APE.